The influence of cultural background on content marketing practices: the approach of Turkish and Lithuanian youth to the main components of content marketing - Kuş, Oğuz (Information & Media, 2017)
This research paper mainly aims to illuminate the influence of cultural differences on certain components of the content marketing process. The study has a descriptive research approach. In order to collect research data, a digital survey, also in print, was applied to university students both in Turkey and Lithuania. Within the framework of the study, responses of the individuals revealed cultural influences on three vital main content marketing components: the distribution channel, the types of the messages and formats of building engagement with the target audience. Results proved that individuals from both countries have slight differences when it comes to reaching content, consuming it and interacting with it. It is possible to explain this situation on the basis of two factors. The first factor is globalism and the second one is that internet tools create their own usage culture and that individuals have been integrating with those cultures.